Establishment of a rapid method for the detection of Brucella canis based on recombinase-mediated thermostable nucleic acid amplification technology - Song, Shao-Zheng; Li, Zi-Yuan; Liu, Yuan-Yuan; Wu, Ying-Chao; Yu, Kang-Ying; He, Zhengyi (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo establish a rapid detection method for canine brucellosis using recombinase-aided amplification (RAA) technology.MethodsThe outer membrane protein 25 gene fragment (Omp25) of Brucella canis was targeted. Primers and fluorescent probes were designed and synthesized, and recombinant plasmids were constructed as standards. The RAA assay was optimized by screening primers and establishing a fluorescent reaction system. Sensitivity was analyzed using plasmid standards with varying copy numbers. Specificity was tested using genomes from Brucella canis, Brucella suis, Brucella melitensis, Brucella abortus, Staphylococcus aureus, pathogenic Escherichia coli, Salmonella enteritidis, Shigella spp., Proteus mirabilis, and Listeria monocytogenes. Reproducibility was evaluated using plasmid standards from the same and different batches.ResultsThe optimized RAA system used primers bOmp25-F2/bOmp25-R2 and probe bOmp25-P, with a constant reaction temperature of 39°C for 15 minutes. The detection sensitivity was 1 copy/μL. No cross-reaction was observed with other Brucella species or pathogenic bacteria, indicating high specificity. Intra-batch variability was below 1.00%, and inter-batch variability was below 2.00%. The positive detection coincidence rate of RAA was significantly higher than that of commercial real-time fluorescence quantitative PCR (100% VS 86.96%, P<0.05).ConclusionThe RAA-based rapid detection method for Brucella canis is suitable for clinical rapid testing. It offers advantages such as quick detection, high sensitivity, strong specificity, and good reproducibility. This method provides new insights for the rapid detection of canine brucellosis and the precise diagnosis of other pet diseases, making it suitable for promotion and application.